(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article provides methodological recommendations for the prevention of adolescent computer addiction. In the article, measures aimed at meeting social needs (the need to belong to a group, the need for respect) and the intellectual needs of adolescents can serve as a means of preventing Internet addiction in adolescents.